Community Service Innovation of STKIP PGRI Sumenep Lecturers: Using Canva to Develop PE Modules in Elementary Schools - Masodi, Masodi; Ramadhani, Dika Desita; Santoso, Citra Reksi; Agustin, Faikotul Wulan; Darmayanti, Rani (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
In order to improve the quality of physical education and sports in elementary schools, lecturers of STKIP PGRI Sumenep initiated community service through the development of learning modules based on the Canva application. The background of this activity is the need for innovative and effective educational resources to support interactive learning, in accordance with technological developments and the needs of modern education. By using the Action Research method, this activity involved 5 Lecturers and 3 physical education teachers in Sumenep Regency as subjects. Data collection was carried out through in-depth interviews, participatory observation, and document analysis. This community service approach includes intensive training and ongoing mentoring to improve teachers' abilities in designing interactive learning modules with Canva. The data analysis technique used is qualitative descriptive analysis to understand changes in teacher competency before and after training. The results show a significant increase in creativity and technical skills of teachers in using Canva, which has a positive impact on the effectiveness and motivation of student learning. The conclusion of this study is that the integration of technology in the development of physical learning modules can improve the quality of education and provide a more enjoyable learning experience for students.